Research Of Modeling Environments For Microprocessor Systems With Additional Modules Of Cryptographic Information Protection - Klimushyn, P.S.; Kolisnyk, T.P.; Lanovoi, O.F.; Mozhaiev, M. O. (Bionics of Intelligence, 2020)
The field of application of the protected microprocessor systems includes information security functions: authentication of subjects and objects of information interaction, information encryption, integrity control, access control,key management. Today, the urgent task is to establish the security of microprocessor-based systems using a variety ofcomputer simulation software environments. The work analyzes the most effective and affordable computer simulation programs for microprocessor systems and gives practical recommendations for their use. It has been shown thatthe most powerful computer-aided design system is the Proteus software suite which allows simulating the operationof various microprocessor devices with support for several microcontroller families from different manufacturers. Themain advantages include: performing all stages of development in a single environment; the ability to write, debug, andtest firmware, generate diagnostic messages to find programming errors. Using Multisim in the educational processmakes it possible to: review and change the status of the register content, program memory and data, stack cells andbit configuration; visualize the result of the execution of a single command or a program as a whole; demonstrate thepractice of joint use of languages C and Assembler in one project in order to optimize the program; to study the basics ofoperation and features of peripheral devices functioning. However, the limited set of microcontrollers in the Multisimprogram imposes significant restrictions on the possibility of using it for development of real projects. The computersimulation program TINA has a russified interface that is much easier compared to the Proteus with an ability to enter allthe information about the created project into one file. Compared to Multisim, the TINA library contains significantlymore microcontroller models, and the built-in programmer allows modifying programs and observing the results. Beingable to use the free version of TINA-TI and having an online version of TINACloud using cloud technologies makes thisprogram very useful for education. Web service offers many educational resources and the ability to perform research onthe design of microprocessor systems.